PK20, a new opioid-neurotensin hybrid peptide that exhibits central and peripheral antinociceptive effects - Tsuda Yuko; Van den Eynde Isabelle; Ballet Steven; Kosson Piotr; Kleczkowska Patrycja; Tourwé Dirk; Lipkowski Andrzej W (Molecular Pain, 2010)
Abstract Background The clinical treatment of various types of pain relies upon the use of opioid analgesics. However most of them produce, in addition to the analgesic effect, several side effects such as the development of dependence and addiction as well as sedation, dysphoria, and constipation. One solution to these problems are chimeric compounds in which the opioid pharmacophore is hybridized with another type of compound to incease antinociceptive effects. Neurotensin-induced antinociception is not mediated through the opioid system. Therefore, hybridizing neurotensin with opioid elements may result in a potent synergistic antinociceptor. Results Using the known structure-activity relationships of neurotensin we have synthesized a new chimeric opioid-neurotensin compound PK20 which is characterized by a very strong antinociceptive potency. The observation that the opioid antagonist naltrexone did not completely reverse the antinociceptive effect, indicates the partial involvement of the nonopioid component in PK20 in the produced analgesia. Conclusions The opioid-neurotensin hybrid analogue PK20, in which opioid and neurotensin pharmacophores overlap partially, expresses high antinociceptive tail-flick effects after central as well as peripheral applications.